Seasonal variations in psychiatry outpatient service utilization in a tertiary health care center in subtropical arid regions of northwestern India - Meena, Parth S.; Sharma, Anubhuti; Maurya, Ayush; Bansal, Varun (Indian journal of psychiatry, 2024)
Background: Research on climatic parameters contributing to psychiatric disorder seasonality is limited, particularly in subtropical, arid climates like Rajasthan, necessitating investigation into seasonal variations in psychiatric disorder incidence in the region. This study investigates seasonal variations in psychiatric disorder prevalence over 2 years at a Rajasthan tertiary healthcare center, aiming to uncover links with climatic factors. Aims: To investigate seasonal variations in the utilization of outpatient psychiatry services and elucidate potential determinants contributing to these temporal variations. Settings and Design: This is a hospital-based study. A retrospective chart review of all new patients who utilized psychiatry outpatient services from July 2021 to July 2023 was conducted. Methods and Material: Data were gathered from psychiatric outpatient records of adults (July 2021 to July 2023), diagnosed using ICD-10. Seasons were categorized: winter (November-January), spring (February-April), summer (May-July), and rainy (August-October). Meteorological data, temperature, and day length were obtained. Statistical analyses, including Pearson correlation and Chi-square fitness, assessed seasonal associations with psychiatric disorders. Results: A total of 29,164 patient records were observed. Depression correlated with temperature and photoperiod. Mania peaked in August, linked to day length. Schizophrenia showed seasonal variation without environmental correlation. Anxiety peaked in March with no statistical significance. Obsessive compulsive disorder cases spiked in June, moderately correlated with temperature and photoperiod. Alcohol-related disorders peaked in December, while opioid dependence remained steady. Cannabis-induced psychosis peaked in summer, strongly correlated with temperature and day length. Headaches surged in August, positively correlated with temperature and day length. Conclusions: This study reveals complex relationships between seasonality, environmental factors, and psychiatric disorders, emphasizing their importance in mental health research and practice.